Correlation between field electrical resistivity and geotechnical SPT blow counts at tropical soils in Brazil - Gonçalves, Juliana Teles Diniz; Botelho, Marco Antonio Barsottelli; Machado, Sandro Lemos; Netto, Leonides Guireli [UNESP] (Elsevier, 2021)
The joint application of geophysical investigations, non-invasive methods, and geotechnical investigations, invasive methods, in order to interpret the geological features in subsurface has been increasingly accepted, however, the correlation between the values collected by the geophysical methods and the direct investigative techniques have been developed in recent years. The obtained linear relationships are site specific and complementary studies are needed to establish their validation and limitations for each site. In this study, Electrical Resistivity Tomography (ERT) was used with Standard Penetration Test (SPT) for geotechnical investigation at three hillslope sites with different tropical soil properties in Bahia, Brazil. The results from thirteen boreholes were analyzed against data from 2D inverted sections. Linear fitting successfully correlates resistivity and NSPT for one borehole. Correlations of electrical resistivity and NSPT values were also performed using soils with similar compositions and physical characteristics, which showed good results. The coefficient of correlation (R) was 0.94. In addition, results the fitting slope coefficient seems to be dependent of soil genesis (lithology, texture and clay content variation) scription obtained in SPT surveys.
Keywords: Correlation; Electrical resistivity tomography (ERT); Soil resistivity; SPT; Tropical soils